Estudo comparativo entre ligas resistentes ao desgaste abrasivo, aplicadas por soldagem, em chapas metálicas para fabricação de placas anti desgaste - Ricardo Vinicius de Melo Leite (2008)
The metal alloys deposited by welding on the components surface, with the objective of protection against wear and the consequent increase in the lifetime of parts and equipments, have been used extensively in the consumer products industry and sectors of Mining and Sugar & alcohol. The abrasive wear on parts and equipments represents one of the main depreciation factors of capital and the major source of expenditure onmaintenance in industries. For the application of the coating by welding, flux cored wire has been a viable alternative, because of its high productivity and high weld quality, replacing in part, the use of the stick electrode. The objective of this work is to make a comparative study of the abrasive wear resistant coating deposited by welding withselfshielded cored wires of three metal alloys used in industry, first the Fe-Cr-C alloy, the second the Fe-Cr-C alloy with niobium and boron addition and the third the Fe-Cr-C with niobium addition. The wear resistant coatings, known as hardfacing were deposited on carbon steel plates, with the same parameters and procedures of welding. Thesamples were obtained by cutting and grinding and were subjected to abrasive wear tests, in a Rubber Wheel apparatus, according to procedure established by ASTM G65- 91. The results showed that the Fe-Cr-C alloy with Niobium and Boron addition presented superiority in terms of wear resistence.